2018
DOI: 10.1002/ecy.2537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biotic interactions on tropical tree performance depend on abiotic conditions

Abstract: Predicting biotic responses to environmental change requires understanding the joint effects of abiotic conditions and biotic interactions on community dynamics. One major challenge is to separate the potentially confounding effects of abiotic environmental variation and local biotic interactions on individual performance. The stress gradient hypothesis (SGH) addresses this issue directly by predicting that the effects of biotic interactions on performance become more positive as the abiotic environment become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 88 publications
(227 reference statements)
0
10
0
Order By: Relevance
“…The stress-gradient hypothesis (Bertness & Callaway, 1994) postulates that positive interactions will be predominant in communities exposed to harsher environmental conditions, while negative interactions will be more typical of communities under mild environmental conditions. This hypothesis has been corroborated by a wide range of studies on plant communities (Casalini & Bisigato, 2018;Kjaer et al, 2018;Muscarella et al, 2018 et al, 2014). However, although neighbour facilitation is probably an important mechanism among poikilohydric organisms (i.e.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The stress-gradient hypothesis (Bertness & Callaway, 1994) postulates that positive interactions will be predominant in communities exposed to harsher environmental conditions, while negative interactions will be more typical of communities under mild environmental conditions. This hypothesis has been corroborated by a wide range of studies on plant communities (Casalini & Bisigato, 2018;Kjaer et al, 2018;Muscarella et al, 2018 et al, 2014). However, although neighbour facilitation is probably an important mechanism among poikilohydric organisms (i.e.…”
Section: Introductionmentioning
confidence: 72%
“…Biotic interactions play an important role in maintaining biodiversity (Bascompte & Jordano, 2007;Muscarella et al, 2018), and neighbour interactions are among the main forces shaping plant communities (Gavini et al, 2019;Grant et al, 2014). These interactions are one of the forces shaping spatial patterns, and analysing such patterns can be a powerful approach to deduce the processes determining community structure (Alados et al, 2017;Dale, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, available space and resources for each individual as well as intra- and interspecific interactions to some extent can be reflected by stem abundance in communities ( Fortunel et al, 2018 ). For example, high stem abundance was observed to have increased competition for light and space among individuals ( Muscarella et al, 2018 ). In addition, the more individuals hypothesis ( Gaston, 2000 ) also demonstrated that stem abundance can promote species richness ( Madrigal-González et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The causes, however, cannot be discerned from this study. Biotic interactions, e.g., interand intraspecific neighborhood interactions through natural enemies, can mediate site-to-site variation in functional diversity (Lasky et al, 2014;Muscarella et al, 2018Muscarella et al, , 2016. Whether neighborhood interactions differ between fragments and contiguous forests remains poorly explored (Krishnadas et al, 2018a).…”
Section: Trait Covariance In Fragmentsmentioning
confidence: 99%